Right Sided Aortic Arch with Aberrant Left Subclavian Artery from Kommerell’s Diverticulum, a Cause of Persistent Dysphagia in an Adult: A Case Report - Regmi, Pradeep R; Amatya, Isha; Kafle, Bipula; Kayastha, Prakash; Paudel, Sharma (Journal of Institute of Medicine Nepal, 2021)
Congenital variations and anomalies of the aortic arch are important entity in vascular imaging. Most of them are asymptomatic. About 30-40% presents with tracheo-oesophageal symptoms like dyspnea and dysphagia. A 27 year-old female presented with persistent dysphagia for 6 months duration and cause of persistent dysphagia was the right sided aortic arch with aberrant left subcalvian artery from Kommerell’s diverticulum. The diagnosis was made through combination of chest X-Ray, echocardiography, non-ionic contrast swallow and Computed Tomography angiography. Non-invasive modalities (CT and MR Angiography) play an important role in diagnosis and pre-operative surgical planning providing relationship with the surrounding structures especially trachea and esophagus.